ANALISIS INOVASI PELAYANAN PUBLK PADA DINAS KOMUNIKASI, INFORMASI, STATISTIK, DAN PERSANDIAN KOTA SEMARANG ( Pusat Informasi Publik Sebagai Top 99 Inovasi Pelayanan Publik Tahun 2016) - Bunga Rismaya Riantika; Hardi Warsono (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Public service innovation is a breakthrough type of public service that is an original creative idea or adaptation that give benefits for society directly or indirectly. Public service innovation competition is anually designed by Ministry of State Apparatus Utilization and Bureaucratic Reform. This competition is a form One Agency program, One Innovation (OAOI) that requires each agency, ministry, institute, provincial government, city create innovation every year. This study is conducted at Communication, Information, Statistic and Encryption Service in Semarang City. Public Information Center is a form of service innovation created by Diskominfo in cooperation with several related parties. This study based on achievement that achieved by PIP in Semarang City that is “3 in 1” Public Service, Public Information Center Semarang City as Top 99 Public Service Innovation 2016. Based on study, there are still some obstacles in implementation of innovation in Diskominfo Semarang city. Therefore, a recommendation that can be given is addition of technology information units (computer) that filled by data information so that society can access directly and addition of facilities that ease the society.